Everyone is searching for it and those who acquired it enjoy better mental health: a latent profile analysis of Chinese adolescents’ meaning in life - Zhou, Xiaohua; Yu, Lu; Deng, Chen; Ren, Yaoxiang; Du, Meng (Frontiers in Psychology, 2024)
Objective One factor associated with rising rates of depression and anxiety among youth is a lack of meaning in life (MIL). The importance of living a meaningful and purposeful life cannot be overstressed, especially for adolescents who are in a critical life stage and have recently experienced a 3-year-long global health crisis, namely the COVID-19 pandemic. Although previous studies have examined adolescents’ MIL, the majority of them adopted a variable-centered approach. The present study adopts a person-centered approach to investigate the updated MIL among Chinese adolescents in the aftermath of the COVID-19 pandemic, the demographic factors related to profile classification, and the differences in mental health among adolescents in different MIL classes. Methods A questionnaire assessing MIL, depression, anxiety, stress, and demographic information was administered to 1,196 Chinese adolescents (mean age = 13.07 ± 0.58; 44.73% were female individuals). A three-step latent profile analysis was conducted. Results and discussion This study revealed that (1) adolescents can be categorized into three classes: high MIL, medium MIL, and low and searching MIL. (2) Adolescents from intact families with higher educated mothers were more likely to be classified as high MIL class rather than low MIL class. Furthermore, (3) adolescents with high MIL experienced the best mental health outcomes, those with medium MIL experienced moderate mental health, and those with low MIL, who were still searching for MIL, exhibited the poorest mental health. External support may be necessary in the search process for Chinese adolescents. Future research could explore the process of searching for MIL and identify the challenges adolescents encounter when developing their sense of MIL.